A Comparative Evaluation of Two Adhesion Promoters on Bonding of Orthodontic Brackets to Fluorosed Enamel: An in vivo Study - Grover, Seema; Sidhu, Maninder Singh; Prabhakar, Mona; Dabas, Ashish; Malik, Vikas; Yadav, Puneet; Diwakar, Rohan; Kumar, Sandeep (Journal of Orofacial Research, 2015)
Bonding on fluorosed enamel is a challenge for orthodontists due to frequent bond failures at compromised enamel interface. Objectives: Aims of this in vivo study were to evaluate and compare effects of two adhesion promoters, Enhance LC and All-Bond 3, on bonding to fluorosed enamel in orthodontic patients.Materials and methods: Clinical study included 18 patients with age group range of 13 to 25 years. Two bond promoters Enhance LC (Reliance, Itasca, IL, USA) and All-Bond 3 (Bisco, Schaumburg, IL, USA) were used to test bond failure rate in all patients using split mouth technique. Enhance LC and All-Bond 3 were used randomly in upper right and lower left quadrants or vice versa to remove bias. Total 264 severely fluorosed teeth were bonded and monitored for 9 months. Bond failures were recorded in log book. Chi-square test was done to compare number of bracket failures between two groups and number of patients experiencing at least one bond failure. Results: Study showed significant difference between bond failure rate of two adhesion promotors (P–0.039%). Bond failure rate was 3.03% in Enhance LC group and 9.1% in All-Bond 3 group. Number of patients experiencing bond failure rate were also statistically significant (P–0.034). Conclusion: Study showed clinically acceptable bond failure rate with Enhance LC compared to All-Bond 3 group. Hence, use of Bond promoters is suggested to be mandatory before bonding in patients with fluorosed enamel.